Kualitas Semen Cair Asal Epididimis Kerbau Belang dalam Bahan Pengencer Andromed yang Mendapat Penambahan Sukrosa - M Surachman; . Herdis; . Yulnawati; M Rizal; H Maheshwari (Faculty of Animal Science, Bogor Agricultural University, 2009)
The aim of this research was to observe the quality of spotted buffalo epididymal sperm after storage at 4 °C as liquid semen for 12 and 24 hours in andromed containing sucrose 0.2% and 0.4%. Sperm was collected from epididymal tissues by combination of slicing and pressing methods. The parameters observed were the percentage of progressive motility and live sperm. The results showed that the percentage of progressive motility of the liquid semen after storage for 12 hours in andromed (A), andromed + sucrose 0.2% (P1) and andromed + sucrose 0.4% (P2) were 48.33%; 53.33% and 55% (P>0.05), respectively. In addition, the percentage of motility after 24 hours of storage in those extenders were 45%; 46.67% and 46.67% (P>0.05), respectively. The percentage of live sperm in A, P1 and P2 after 12 hours of storage were 70.33%; 73% and 73.33% while after 24 hours of storage, the percentage of live sperm in those extenders were 66.33%; 68.67% and 69.67%, respectively. In conclusion, the addition of 0.2% and 0.4% sucrose in andromed extender could maintain the quality of the spotted buffalo epididymal sperm after storage for 12 and 24 hours at 4 °C. Key words: epididymal sperm, spotted buffalo, sucrose, liquid semen, andromed